Exploring Hermeneutic Through Lyrics of the Song “Akhir Tak Bahagia”: A Case on Critical Discourse Analysis - Ratna saputri saragih; Klara kristina Malaub; Nikerian W, Manik; Widya Ambarita; Nopaulina Sinagae; Herman Herman (Journal of English Language and Education, 2023)
The goal of this research was focused more on Wilhelm Dilthey's hermeneutic theory to examine the lyrics of the song "Akhir Tak Bahagia" with the concept of Erlebnis (living experience), the main reason why the author uses the science of hermeneutics because hermeneutics has an Erlebnis study process (living experience), which aims so that the results of this research can be a reflection of phenomena that occur in society according to the object studied. The data analysis technique used was descriptive qualitative analysis technique. The study of the structure of language units is a heuristic step to find meaning through linguistic signs, namely as follows. Based on the study of the language units, 92 data were obtained in the form of words, 8 data of phrases, 1 data of sentences, and from this study no clauses were obtained because in the lyrics do not describe the unit clause. Based on the results of the researcher's analysis of the text of the song "Akhir Tak Bahagia" by Misellia Ikwan to answer what is in the problem formulation, there are several points in the process of Wilhem Dilthey's hermeneutic analysis of the text of the song "Akhir Tak Bahagia", these points, namely: Erlebnis (living experience).